The “New Spain” and the Spanish Falange in Portugal During the Spanish Civil War: Information and Propaganda - Pena Rodríguez, Alberto (Revista de Historia Social y de las Mentalidades, 2024)
This article aims to recover some of the most interesting aspects of the propaganda activity of the Spanish Falange in Portugal during the Spanish Civil War. The Spanish fascist organization, integrated into Franco's National Movement, developed a rearguard strategy to legitimize the military coup against the Second Spanish Republic. It recruited volunteer fighters for the insurgent army and fund-raising campaigns to finance its cause against Spanish democracy. Through a qualitative methodology and using primary sources of a diplomatic and newspaper nature, both Spanish and Portuguese, the functioning and media projection of the Falange in Portugal is analyzed and described.
Keywords: Spanish Falange; Spanish Civil War; Propaganda; Portugal